The Effect of Financial Literacy, Financial Planning, and Impulsive Buying Behavior on Personal Financial Management (A Case Study of Timor-Leste International Students in Malang) - Abrantes, Sonia Pacheco; Sudaryanti, Dwiyani; Efendi, Erfan (e_Jurnal Ilmiah Riset Akuntansi, 2026)
Effective financial management is crucial for students, especially those studying abroad, as they face complex economic environments. Based on this condition this study examines the influence of financial literacy, financial planning, and impulsive buying behavior, both partially and simultaneously, on personal financial management among Timor-Leste international students in Malang, Indonesia. A quantitative correlational approach was employed, surveying 97 students selected through purposive sampling from seven universities. Data were collected via online questionnaires and analyzed using multiple linear regression. The results show that financial literacy has a positive but non-significant effect on personal financial management, while financial planning and impulsive buying behavior have positive and significant effects on personal financial management, with regression coefficients of 0.243 and 0.294, respectively. Simultaneously, the three variables significantly influence personal financial management, indicating that combined knowledge, planning, and controlled spending behaviors determine the quality of financial management. These findings highlight the importance of financial planning and behavioral management in fostering effective personal financial management and provide practical implications for educational institutions in enhancing students’ financial decision-making skills.Keywords: Financial literacy, financial planning, impulsive buying, personal financial management.